IMPACT OF CASTE ON WOMEN'S POLITICAL PARTICIPATION IN INDIA - Rekha Kumari (International Journal of Multidisciplinary Research and Studies, 2021)
Women make up about half of India's population and make significant contributions to human development. Women are an essential part of the development dialectics and provide both the source and the energy for development. However, massive shackles of cultural preconceptions have strengthened the rigidity of the patriarchal culture and delineates the involvement of women in the development discourse more systematically around the world. The patriarchal society reduces the opportunities for women to advance their status, particularly in countries with lower levels of education and cultures that are more conservative, such as India. In spite of the fact that there have been a large number of affirmative actions, Constitutional privileges, international treaties protection, various women's rights movements, educational development of women, and feminism driven protest against the vulnerability, significant changes have been made in educational development, economic empowerment, and social recognition to some extent but not to an adequate level. To a considerable extent, however, women's empowerment is limited to their representation in the domains of decision making and policy making. Therefore, the political participation of women became necessary to guarantee the empowerment in all of the spheres of activity and to ensure that the gender dimension of the requirements could be addressed and enacted as policies for the empowerment of women who have been subjected to humiliation and dishonour in public spheres. Not only does the Constitution guarantee women equal voting rights, but it also substantially acknowledges the contributions women have made to the country.